2012
DOI: 10.1186/1475-2867-12-45
|View full text |Cite
|
Sign up to set email alerts
|

Unique functions of CHK1 and WEE1 underlie synergistic anti-tumor activity upon pharmacologic inhibition

Abstract: BackgroundInhibition of kinases involved in the DNA damage response sensitizes cells to genotoxic agents by abrogating checkpoint-induced cell cycle arrest. CHK1 and WEE1 act in a pathway upstream of CDK1 to inhibit cell cycle progression in response to damaged DNA. Therapeutic targeting of either CHK1 or WEE1, in combination with chemotherapy, is under clinical evaluation. These studies examine the overlap and potential for synergy when CHK1 and WEE1 are inhibited in cancer cell models.MethodsSmall molecules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
79
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 37 publications
9
79
0
2
Order By: Relevance
“…32 In conclusion, our study provides clinical evidence that AZD1775 enhances the antitumor efficacy of carboplatin in patients with TP53-mutated ovarian cancer resistant to first-line therapy and suggests that AZD1775 plus carboplatin may outperform first-line platinum-based chemotherapy in these patients. On the basis of these encouraging results, further development starting with a randomized phase II or III study is warranted in this particular patient group and in other p53-deficient tumors to substantiate the true value of AZD1775.…”
Section: Discussionmentioning
confidence: 85%
“…32 In conclusion, our study provides clinical evidence that AZD1775 enhances the antitumor efficacy of carboplatin in patients with TP53-mutated ovarian cancer resistant to first-line therapy and suggests that AZD1775 plus carboplatin may outperform first-line platinum-based chemotherapy in these patients. On the basis of these encouraging results, further development starting with a randomized phase II or III study is warranted in this particular patient group and in other p53-deficient tumors to substantiate the true value of AZD1775.…”
Section: Discussionmentioning
confidence: 85%
“…[37][38][39][40] Davies et al performed a medium throughput screen to the Chk1 inhibitor AR458323 and identified WEE1 as their top hit in one lung cancer and two prostate cancer cell lines. 38 In a separate study by Carrassa et al, high throughput siRNA screening identified WEE1 kinase to be synthetically lethal with the small molecule Chk1 inhibitor PF-00477736 in ovarian cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Although broadly synergistic combinations may seem the most attractive, we suspect that many of these combinations may not be well tolerated in mice and human patients. Notably, the mTOR inhibitor/Wee1 inhibitor combination was well tolerated at the respective MTDs while the Chk1 inhibitor/Wee1 inhibitor was not (11,17). Context-dependent combinations, especially those that combine drugs targeting two different pathways, are less likely to have overlapping toxicities.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 538 combinations tested, 287 ($50%) were synergistic in at least one cell line and 178 ($30%) were antagonistic in at least one cell line. We identified few broadly synergistic combinations including the Wee1 inhibitor combined with the Chk1 inhibitor (11) and PARP inhibitor combined with temozolimide (12, 13). Context-dependent synergistic drug combinations were also identified, including the mTOR inhibitor/AKT inhibitor combination and mTOR inhibitor/ERK inhibitor combination.…”
Section: Landscape Of Combination Synergy and Responsementioning
confidence: 99%